2021
DOI: 10.1029/2021gl093799
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Forest Height and Aboveground Biomass by Integrating ICESat‐2, Sentinel‐1 and Sentinel‐2 Data Using Random Forest Algorithm in Northwest Himalayan Foothills of India

Abstract: Forest canopy height, which is the mean height of the top surface of a forest's canopy, is a significantly important indicator of biomass and carbon stock (Li, Niu, et al., 2020;Zhang et al., 2016) and is expected to be the key to the accurate assessment of forest biomass (Alexander et al., 2018;Kearsley et al., 2013). Remote sensing (RS) data integrated with in-situ measurements has become an effective approach for estimation of forest aboveground biomass (AGB) and carbon stocks (Nandy et al., 2019). Both pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(44 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Additionally, while smart phone GPS measurements are improving with most being at best accurate to within 4 m, an analysis of GO data found an average location accuracy of 14.5 m. Given the 13 m ICESat-2 photon pulse footprint, this means that GO Trees measurements within the footprint may not be resolvable or may be misleading. Similar results have been found in other studies (Li et al 2020, Nandy et al 2020, but additional studies should expand the types and amount of tree cover.…”
Section: Using Go Trees Data With Icesat-2supporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, while smart phone GPS measurements are improving with most being at best accurate to within 4 m, an analysis of GO data found an average location accuracy of 14.5 m. Given the 13 m ICESat-2 photon pulse footprint, this means that GO Trees measurements within the footprint may not be resolvable or may be misleading. Similar results have been found in other studies (Li et al 2020, Nandy et al 2020, but additional studies should expand the types and amount of tree cover.…”
Section: Using Go Trees Data With Icesat-2supporting
confidence: 90%
“…An essential component in understanding ICESat-2's performance in measuring tree height is the comparison to ground-based measurements. As an example, a recent study (Nandy et al 2020), found a 1.1 m root mean square error (a measure of the differences between values predicted by a model and the values observed), between field-measured and ICESat-2 tree heights for trees that ranged from 14.2 to 32.4 m. This error information is critical to utilizing ICESat-2 data for aboveground biomass estimates or global land cover uses (Narine et al 2020).…”
Section: Introduction 1why Measure Tree Heightmentioning
confidence: 99%
“…Many studies have analyzed the spatiotemporal variations of vegetation AGB and their responses to climate change (Stegen et al, 2011 ; Shi et al, 2015 ; Castanho et al, 2020 ; Zhou et al, 2021 ). However, most of these studies focused on grassland and forest ecosystems, and only a few were conducted on marsh ecosystems (Flannigan et al, 2000 ; Shen et al, 2016 , 2022a ; Dai et al, 2021 ; Konings et al, 2021 ; Naik et al, 2021 ; Nandy et al, 2021 ; Qin et al, 2021 ; Wang et al, 2022b ). Compared with other ecosystems, marsh ecosystems have unique environmental conditions, which may lead to different influences of climate change on AGB (Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the LiDAR data is available as strips for the limited region for airborne missions and is discontinuous for spaceborne missions (Narine et al, 2019;Dubayah et al, 2020;Duncanson et al, 2020) that pose a grave source of uncertainty in biomass estimation. LiDAR canopy height, in combination with other remote sensing techniques, is successfully used to estimate forest AGB with high accuracy levels (Dhanda et al, 2017;Nandy et al, 2021). A combination of spectral variables from Sentinel-2 and ICESat-2 data is used to interpolate canopy height using a random forest algorithm by Nandy et al (2021) that provided an improved estimate of forest height and AGB in sub-tropical forests.…”
Section: Introductionmentioning
confidence: 99%
“…LiDAR canopy height, in combination with other remote sensing techniques, is successfully used to estimate forest AGB with high accuracy levels (Dhanda et al, 2017;Nandy et al, 2021). A combination of spectral variables from Sentinel-2 and ICESat-2 data is used to interpolate canopy height using a random forest algorithm by Nandy et al (2021) that provided an improved estimate of forest height and AGB in sub-tropical forests. However, such similar studies utilizing SAR and LiDAR data for forest AGB estimation in the species-rich Western Ghats located in the tropical regions is very limited.…”
Section: Introductionmentioning
confidence: 99%